Analisis Strategi Layanan Syariah Bank Syariah Indonesia KCP Banjarnegara Perspektif VRIO dan PEST - Adibatunnisa Adibatunnisa; Zahra Ayu Agustin; Neli Nurul Azizah; Yoiz Shofwa Shafrani (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to evaluate the sharia financial service strategy of Bank Syariah Indonesia (BSI) Banjarnegara Branch through the VRIO and PEST approaches, in order to identify internal advantages and external dynamics that affect the competitiveness of the institution. Using a qualitative-descriptive method, this study reveals that BSI Banjarnegara has a sustainable competitive advantage through sharia-based products that are difficult to imitate, a wide community network, and a personal service approach. In addition, the results of the PEST analysis show that political support, stable economic conditions, and the level of community religiosity are great opportunities for the growth of sharia finance in the region, although the level of digital technology adoption is still a challenge. The strategy of strengthening digitalization, education of sharia financial literacy, and product innovation such as Cicil Emas are the main keys in responding to market challenges and increasing financial inclusion. Thus, the results of this study provide a strategic direction for the development of sustainable and adaptive sharia services to changes in the business environment.